Communicating tourism destinations through travel writing: A case study on travel content research in tourism co-creation - Mansfield, Charles; Roberts, Zoë; Potočnik Topler, Jasna (Turyzm/Tourism, 2025)
This research explores the intersection of travel writing pedagogy and professional practice through the creation and analysis of a travel writing portfolio. One of the researchers compiled a portfolio of nine travel texts to test the efficacy of the aim, design, assessment (ADA) apparatus – a tool designed for planning and evaluating travel writing. The study utilised close reading techniques, drawing on established literary and semiotic theories, to analyse the portfolio and assess the role of pedagogic knowledge in professionalizing travel writing. The research highlights the importance of structured, reflective practices in producing travel texts that are both engaging and informative. Additionally, the study advances travel writing methodology by incorporating journaling into a Web 2.0 archive, offering new insights into the dialogic process between researchers and stakeholders. While the study’s limitations include a lack of comparative data, it lays the groundwork for further exploration of travel writing’s pedagogic and professional dimensions. The findings underscore the value of integrating pedagogic theory with practical application, providing a framework for future research and professionalisation of the genre.